(3TQM MeGSI CHj JeGes - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ddg aEfi cfJ cJHJ ddMeGSI TQMkG eSJhai s
(3BNQgG (B:s
(3bGd GHh GdYdGA (B: (3ghJ Cege ef GdCOYjg GdJi CSJYedgG GdYQH Ydi GdYcS hPdc Cf XGgQgG s
(3HChdgG Jedc HJGQjN (B1054(3g`s
(3GdTQM GdUZjQ JJab ai ChdgG eY GdfSNI GdKGfjI HGNJdGa ai HYV GdCdaGXs
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs